Structure-Based Evolution of Subtype-Selective Neurotensin Receptor Ligands - Schaab, Carolin; Kling, Ralf; Einsiedel, Jürgen; Hübner, Harald; Clark, Timothy; Seebach, Dieter; Gmeiner, Peter (ChemistryOpen, 2014)
Subtype-selective agonists of the neurotensin receptor NTS2 represent a promising option for the treatment of neuropathic pain, as NTS2 is involved in the mediation of m-opioid-independent anti-nociceptive effects. Based on the crystal structure of the subtype NTS1 and previous structure-activity relationships (SARs) indicating a potential role for the sub-pocket around Tyr11 of NT(8-13) in subtype-specific ligand recognition, we have developed new NTS2-selective ligands. Starting from NT(8-13), we replaced the tyrosine unit by β2-amino acids (type 1), by heterocyclic tyrosine bioisosteres (type 2) and peptoid analogues (type 3). We were able to evolve an asymmetric synthesis of a 5-substituted azaindolylalanine and its application as a bioisostere of tyrosine capable of enhancing NTS2 selectivity. The S-configured test compound 2a, [(S)-3-(pyrazolo[1,5-α]pyridine-5-yl)-propionyl11]NT(8-13), exhibits substantial NTS2 affinity (4.8 nm) and has a nearly 30-fold NTS2 selectivity over NTS1. The (R)-epimer 2b showed lower NTS2 affinity but more than 600-fold selectivity over NTS1.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.lphch.struct

Structure-guided development of heterodimer-selective GPCR ligands - Hübner, Harald; Schellhorn, Tamara; Gienger, Marie; Schaab, Carolin; Kaindl, Jonas; Leeb, Laurin; Clark, Timothy; Möller, Dorothee; Gmeiner, Peter (Nature Communications, 2016)
Crystal structures of G protein-coupled receptor (GPCR) ligand complexes allow a rational design of novel molecular probes and drugs. Here we report the structure-guided design, chemical synthesis and biological investigations of bivalent ligands for dopamine D-2 receptor/neurotensin NTS1 receptor (D2R/NTS1R) heterodimers. The compounds of types 1-3 consist of three different D2R pharmacophores bound to an affinity-generating lipophilic appendage, a polyethylene glycol-based linker and the NTS1R agonist NT(8-13). The bivalent ligands show binding affinity in the picomolar range for cells coexpressing both GPCRs and unprecedented selectivity (up to three orders of magnitude), compared with cells that only express D(2)Rs. A functional switch is observed for the bivalent ligands 3b,c inhibiting cAMP formation in cells singly expressing D(2)Rs but stimulating cAMP accumulation in D2R/NTS1R-coexpressing cells. Moreover, the newly synthesized bivalent ligands show a strong, predominantly NTS1R-mediated beta-arrestin-2 recruitment at the D2R/NTS1R-coexpressing cells.